Significance of tests of iron nutrition in pregnancy. Issue 2 (March 1966) - Metz, J.; Turchetti, L.; Combrink, B.; Krawitz, S.
Abstract : Tests of iron and folate nutrition have been carried out in early pregnancy and at delivery in 63 Bantu females. Accepted normal values for serum iron, and percentage saturation of transferrin, but not for unsaturated iron-binding capacity, for non-pregnant subjects were found to apply equally well in pregnancy. Concomitant folate deficiency in early pregnancy did not render tests of iron deficiency less valid. The unsaturated iron-binding capacity, percentage saturation, and marrow iron stores in early pregnancy all showed a significant correlation with the haemoglobin value at term. Patients with normal marrow iron stores and a percentage saturation of transferrin of 20 or more at or before the 24th week are unlikely to become anaemic from iron deficiency during pregnancy.